2008
DOI: 10.1080/14616680701825230
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Cities Based on Tourism Supply and Climatic Conditions in Turkey

Abstract: Tourism has become a major sector in Turkey. The key to continued attraction of visitors to the country in significant numbers is a careful coordination of marketing and planning of tourism supply resources. These supply resources of tourism certainly include favourable climate and climatic elements. The nature of spatial distribution of resources does affect the dispersion of demand in the country. This current study attempts to classify cities based on their supply indicators and establish the connection bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 27 publications
1
27
0
2
Order By: Relevance
“…Tourism is a particularly climate-sensitive economic sector, considering that climate change affects a number of key factors pertinent to the tourism industry [28]. Climate plays an important role in tourism, especially on destination choice and the timing of travel [29][30][31]. Additionally, Taiwan faces changeable weather conditions due to its unique geographic location, which makes the indicator of climatic factor extremely important when considering the sustainable development of coastal tourism.…”
Section: Resultsmentioning
confidence: 99%
“…Tourism is a particularly climate-sensitive economic sector, considering that climate change affects a number of key factors pertinent to the tourism industry [28]. Climate plays an important role in tourism, especially on destination choice and the timing of travel [29][30][31]. Additionally, Taiwan faces changeable weather conditions due to its unique geographic location, which makes the indicator of climatic factor extremely important when considering the sustainable development of coastal tourism.…”
Section: Resultsmentioning
confidence: 99%
“…In the same way, some studies have reported that the weather is a significant part of travel decision making and overall tourist gratification [3][4][5]. Kozak et al [6] described the climate as playing a major resource role in beach tourism. Martin [7] reported that the climate has a role as a facilitator, making tourism activities enjoyable.…”
Section: Introductionmentioning
confidence: 95%
“…The latter two reflect social norms and practices and the impact of various holidays. However, weather and climate not only impact the decision to travel to a particular destination (Kozak, Uysal, & Birkan, 2008), but are also key factors that affect the travel experience (Scott & Lemieux, 2010) and as a result determine subsequent visitation (Wilson & Becken, 2011). Climate refers to the meteorological long-term average conditions that are characteristic of a location, while weather is the state of the atmosphere in a given climate at a particular point in time and determines the participation rate (Moreno, 2010).…”
Section: Introductionmentioning
confidence: 99%